2015
DOI: 10.1016/j.ejmech.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of new GEQ derivatives as inhibitors of InhA enzyme and Mycobacterium tuberculosis growth

Abstract: A series of fluorene-based derivatives was synthesized and evaluated for inhibiting both InhA and Mycobacterium tuberculosis growth. These compounds were inspired by the previously reported Genz-10850 molecule, a good InhA inhibitor, but with a poor activity against M. tuberculosis growth. Structure-activity relationships were performed by introducing the following chemical modifications: 1) the piperazine ring; 2) the amide group; 3) the aryl moiety; and 4) the fluorene moiety. Among these new derivatives, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 47 publications
(31 reference statements)
2
25
0
1
Order By: Relevance
“…Isoniazid was found to interfere with Nicotinamide adenine dinucleotide (NAD)-utilizing enzymes, primarily the enoyl-ACP reductase encoded by the  InhA  gene, leading to the arrest of mycolic acid synthesis, which is essential to  M. tuberculosis [32, 33]. InhA enzyme was chosen based upon its hydrophobic properties that favorably interact with thioamide or thiourea moieties [25]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoniazid was found to interfere with Nicotinamide adenine dinucleotide (NAD)-utilizing enzymes, primarily the enoyl-ACP reductase encoded by the  InhA  gene, leading to the arrest of mycolic acid synthesis, which is essential to  M. tuberculosis [32, 33]. InhA enzyme was chosen based upon its hydrophobic properties that favorably interact with thioamide or thiourea moieties [25]. …”
Section: Resultsmentioning
confidence: 99%
“…The promising compounds 3i and 3s were docked inside the active site of M. tuberculosis enoyl reductase InhA, to predict their possible mode of action. InhA enzyme was chosen as it contains a very hydrophobic site that favorably interacts with thioamide or thiourea moieties [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Esta enzima é essencial para a biossíntese de ácidos micólicos através da via bioquímica de ácido graxo sintase tipo II (FASII) e atua como uma proteína transportadora de grupos acila (ACP) utilizando NADH. 64 67 Recentemente, diversas outras classes de heterociclicos vêm sendo reportadas como potentes inibidores da enzima InhA, como por exemplo derivados tiazólicos identificados por pesquisadores da AstraZeneca. 68 …”
Section: Alvos Envolvidos Com a Biossíntese Da Parede Celularunclassified
“…To improve the membrane permeability, Chollet et al have reported the structural modification of the aryl amide‐based new Genz10850 (GEQ) derivatives derived from fluorene moiety (Fig. ).…”
Section: Small‐molecule Inhibitorsmentioning
confidence: 99%